UPM students' preference for recreation sites in UPM, Serdang - Lim, Xinyee (2016)
UPM students have negative perception toward quality, location, and facilities toward recreation sites in UPM. This was caused by the insufficient of outdoor recreationsites with facilities available to supply the demand of UPM students. This study aimed to determine and to map out designated recreation sites in Universiti Putra Malaysia (UPM) based on students’ preference. A total set of 203 questionnaires were distributed to UPM’s students. The questionnaire was divided into 4 sections, namely Section A which covers students’ preference activities in UPM, Section B and C to obtain the students preference of potential recreation sites, and Section D to obtain social demographic background. Nine activities listed which are jogging, cycling, swimming, futsal, rugby, outdoor workout, picnic, outdoor photography, and sightseeing. The results indicated that jogging was the most popular activity among the UPM students followed by sightseeing. Results show that more than 70% students had chosen Bukit Ekspo as their first choice to pursue their recreational activities and most of them are unaware of any other locations. Based on the students’ preference, several potential recreation sites were recommended and mapped out. Map production using ArcGIS 10.0 is effective to improve people understanding and visualization towards the locations and information absorption.